2001
DOI: 10.1128/iai.69.4.2549-2557.2001
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus ducreyi Associates with Phagocytes, Collagen, and Fibrin and Remains Extracellular throughout Infection of Human Volunteers

Abstract: In a previous study, Haemophilus ducreyi was found in the pustule and dermis of samples obtained at the clinical end point in the human model of infection. To understand the kinetics of localization, we examined infected sites at 0, 24, and 48 h after inoculation and at the clinical end point. Immediately after inoculation, bacteria were found predominantly in the dermis but also in the epidermis. Few bacteria were detectable at 24 h; however, by 48 h, bacteria were readily seen in the pustule and dermis. H. d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
128
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(134 citation statements)
references
References 32 publications
(52 reference statements)
6
128
0
Order By: Relevance
“…Internalized H. ducreyi cells were very sensitive to phagocytic killing by all groups of macrophages, and fewer than 5% of the ingested bacteria survived in macrophages 7 h postinfection. This result is consistent with the previously published study showing that H. ducreyi cells associate with macrophages but are not found intracellularly during human infections (6).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Internalized H. ducreyi cells were very sensitive to phagocytic killing by all groups of macrophages, and fewer than 5% of the ingested bacteria survived in macrophages 7 h postinfection. This result is consistent with the previously published study showing that H. ducreyi cells associate with macrophages but are not found intracellularly during human infections (6).…”
Section: Discussionsupporting
confidence: 94%
“…Experimental pustules and natural ulcers are identical histologically and represent immunological failure. In pustules and ulcers, H. ducreyi colocalizes with macrophages and neutrophils but resists phagocytosis and phagocytic killing and replicates extracellularly (6,7). H. ducreyi secretes two antiphagocytic proteins, LspA1 and LspA2, which inhibit Fc receptor-mediated uptake by macrophage-and neutrophil-like cell lines in vitro (50); a mutant lacking LspA1 and LspA2 expression is attenuated in human volunteers (20).…”
mentioning
confidence: 99%
“…This organism has been shown to attach to extracellular matrix components in vitro, including type I and type III collagen, fibronectin, and laminin (9), and to colocalize with collagen and fibrin in infected sites in human volunteers (8). Several studies have indicated that H. ducreyi can attach to or invade human epithelial cell lines, fibroblasts (2,32,33,54), or keratinocytes (14,24,29) in vitro, although a recent study in the human model for experimental chancroid indicated that, at least through the pustular stage of disease, H. ducreyi apparently remains extracellular (8). It has been suggested that H. ducreyi survives in vivo by resisting phagocytic killing (49), and two other laboratories recently confirmed that H. ducreyi can resist phagocytosis in vitro (1,58).…”
mentioning
confidence: 99%
“…Throughout the papular and pustular stages of experimental infection, H. ducreyi is surrounded by professional phagocytes but remains extracellular (5,6). In vitro, H. ducreyi adheres to the human macrophage-like cell line U-937 but resists phagocytosis (41).…”
mentioning
confidence: 99%